2022
DOI: 10.1108/ajeb-06-2021-0074
|View full text |Cite
|
Sign up to set email alerts
|

Influence of risk propensity, behavioural biases and demographic factors on equity investors' risk perception

Abstract: PurposeInvestor risk perception is a personalized judgement on the uncertainty of returns pertaining to a financial instrument. This study identifies key psychological and demographic factors that influence risk perception. It also unravels the complex relationship between demographic attributes and investor's risk attitude towards equity investment.Design/methodology/approachExploratory factor analysis is used to identify factors that define investor risk perception. Multiple regression is used to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 95 publications
4
14
0
Order By: Relevance
“…Studies that support the dividend signaling theory suggest that the market usually responds positively to the higher dividend events and negatively to the lower dividend events. For example [ 45 ], argues that dividend increase announcement leads to an increase in stock returns of stock-traded companies, whereas the dividend reduction is associated with a decrease in stock returns [ 46 ]. 's research also demonstrates that raising a company's dividend results in a favorable market response; conversely, cutting a dividend had little impact on the market [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies that support the dividend signaling theory suggest that the market usually responds positively to the higher dividend events and negatively to the lower dividend events. For example [ 45 ], argues that dividend increase announcement leads to an increase in stock returns of stock-traded companies, whereas the dividend reduction is associated with a decrease in stock returns [ 46 ]. 's research also demonstrates that raising a company's dividend results in a favorable market response; conversely, cutting a dividend had little impact on the market [ 12 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, if the retail investor is knowledgeable about many elements of his or her investment behaviour as well as the reason for the perceived risks, risk perception may be adjusted (Deb & Singh, 2018;Singh & Bhowal, 2008). With a better knowledge of behavioural finance, industry practitioners can better comprehend investor preferences and provide investing strategies and products that match the investor's risk tolerance (Saivasan & Lokhande, 2022). On the other hand, risk is a component that every investor sees or reacts to.…”
Section: Risk Perceptionmentioning
confidence: 99%
“…According to researchers, prospect theory (Kahneman and Tversky, 1979a) explains that choosing the best and rational decision from various risky and uncertainty situations always depends upon human behaviour rather than maximum utility value due to the imbalance between gains and losses (De Souza et al, 2020;Sharma et al, 2019). When it comes to equity investments, Saivasan et al (2022) found that an individual's investment choice is influenced by the time frame, expectation of returns, and loss aversion that define the risk. There is a link between risk and demographic factors, which may also impact on behaviour.…”
Section: Introductionmentioning
confidence: 99%